Human membership in the large carnivore guild: Was it always “tooth and claw”? - John D. Speth (Quaternary Environments and Humans)
Conventional wisdom holds that when humans began acquiring meat on a regular basis, whether by hunting or by scavenging, they became part of the large carnivore guild and, as a consequence, faced greatly increased levels of potentially life-threatening competition with other predators. This paper offers an alternative view based on fundamental nutritional and metabolic differences between humans, who are descended from primates of largely vegetarian heritage, and hypercarnivores, who are specialized flesh-eaters with a much greater tolerance for protein. Because of these differences, the prey choices and body-part selections made by humans and carnivores, while overlapping, are not isomorphic, with the former prioritizing fatty tissues, the latter prioritizing lean muscle. Competition and confrontation are further minimized by the fact that humans forage during the day, while most predators hunt at night. These and other lines of evidence, including numerous examples from early ethnohistoric accounts, suggest that mutual tolerance rather than deadly confrontation may often have been the most prudent and profitable course of action for all concerned.